ON THE STRENGTH AND FRIABILITY OF SERIES PRODUCTS MANUFACTURED BY DIRECT COMPRESSION OF NON-METALLIC GRANULES - Oleksii Gubenia; Oleksandr Zomenko; Serhii Samarchuk; Dumitru Mnerie (Nonconventional Technologies Review, 2025)
The aim Automation is essential in mass production. In the case of products obtained by direct compression of non-metallic powders, along with measures to increase productivity, there is a risk of reducing their quality. The present research represents an unconventional approach to the methodology of studying the friability of pharmaceutical tablets obtained by pressing the filling powders, in correlation with the working regime. The experiment used contributes to determining the impact of the compression cycles and the speed of the rotary table on the strength and friability of the tablets and other qualitative characteristics. The study enables the optimization of manufacturing technologies of pharmaceutical tablets, respecting the strict quality conditions imposed. The modernization of manufacturing technologies involves new approaches to scientific research in the field.